Kinderschutz durch Strafrecht im türkischen Recht - Ünver, Yener (Pravnik, 2015)
The age of children using drugs in Turkey has dropped to much lower levels. For instance, the age of children using artificial drugs was indicated to be 11. In the fight against organized crime more serious steps should be taken, the supervision intensity over children should be increased removing their responsibility from the criminal field. The police measures are as important. The source of the problem should be eliminated and followed by the right development of social policies supported by the criminal law. The topic of child labour contains the same issues and measures outside the criminal law should be prioritised.
Keywords: child; criminal law; kazensko pravo; kazniva dejanja; odgovornost; otroci; policija; Turčija; Turkey